Peran Lembaga Pendidikan Dalam Pengarusutamaan Islam Moderat Sebagai Upaya Melawan Paham Konservatif-Radikal - Amin Maghfuri (TADRIS: Jurnal Pendidikan Islam, 2019)
In recent years, the landscape that shows a conservative tendency in religion has increased significantly. The Islamic Conservatives in Indonesia experienced unexpected and quite surprising growth and development, and perhaps reached its peak in the last 3-5 years. The negative excesses of this conservative tendency are quite worrying and have the potential to disrupt the sustainability of democracy and the integrity of the nation. This research seeks to elaborate efforts to mainstream moderate Islam which is the main agenda of the government (Ministry of Religion) as a step to counter conservative understanding and see how the role of educational institutions there. This research is a qualitative research focusing on the literature study and using a descriptive-analysis approach. The results of this study indicate that in an effort to mainstream moderate Islam, educational institutions play a significant role although not the only determinant. This role can be realized through several aspects such as curriculum and learning processes in educational institutions, supervision and guidance of programs or activities outside the curriculum of educational institutions starting from elementary to high levels, as well as through educational institutions policies.